Therapeutic intervention on stabilisation parameters in patients with trigger points in suboccipital muscles: a case-control study - Gajdoš, Miloslav; Mikuľákova, Wioletta; Uher, Tomáš; Jakub, Čuj; Nechvatal, Pavol; Kendrová, Lucia D. (Wydawnictwo Akademii Wychowania Fizycznego im. Polskich Olimpijczyków we Wrocławiu, 2025)
Introduction. Hypertonus and the presence of trigger points (TrPs) in the suboccipital muscles (sOMs) frequently contribute to cervical proprioception disorders. Impaired cervical proprioception inevitably aﬀects postural stability, which necessitates therapeutic intervention in conjunction with cervical spine therapy. The aim of this study was to examine the inﬂuence of the myofascial release technique (MFR) on stability parameters in patients diagnosed with TrPs in the sOM region.Methods. Twelve patients (eight females and four males, mean age = 37 ± 9.5 years) underwent postural stability assessment using a force platform (Sensor Medica, Rome, Italy) before and after sOM treatment, with a time interval of one hour. The study’s objectivity was supported by a control group comprising healthy participants (seven females and ﬁve males, mean age = 25 ± 3 years).Results. The results indicated signiﬁcant changes in stability parameters immediately after applying the MFR technique, particularly in patients with TrPs in the sOMs.Conclusions. We recommend that patients undergoing MFR treatment maintain a safe position for at least a few minutes to prevent falls and dizziness.
Keywords: posture; cervical spine; stability; proprioception; trigger points